Analysis of Social Media Digital Marketing Strategies for Building Brand Awareness at JNC Cookies Bandung: Analisis Strategi Digital Marketing Melalui Media Sosial Dalam Membangun Brand Awareness Pada JNC Cookies Bandung - Endah Sriwahyuni; Fina Nur Aulia; Siti Maisaroh; Alvina Mulya Damayanti; Herlinda Maya Kumala Sari (Procedia of Social Sciences and Humanities, 2026)
Advancements in digital technology have prompted companies to utilize social media as an effective tool for boosting brand awareness. General Background The rapid shift toward digital communication obliges businesses to refine their marketing strategies. Specific Background In the premium bakery sector, utilizing digital platforms like Instagram, TikTok, and WhatsApp Business becomes vital for market expansion. Knowledge Gap However, comprehensive evaluations using the modern 9P Marketing Mix framework within literature-based studies remain scarce. Aims This study examines the digital marketing execution of JnC Cookies Bandung to enhance brand exposure through six core marketing dimensions. Results Findings indicate that high visual quality, competitive pricing, prompt interaction, and seamless transaction processes effectively elevate consumer recognition. Novelty This research provides a synthesized qualitative evaluation linking modern marketing mix components directly to social media practices in food enterprises. Implications Consequently, practitioners can optimize digital channels while researchers obtain a structured framework for evaluating digital marketing performance. Key Findings Highlights Integration of visual platforms enhances brand recognition and customer perception. Premium quality combined with transparent pricing models solidifies market positioning. Interactive communication channels accelerate consumer engagement and long-term loyalty.